THE EFFECT OF ELDERLY ACADEMIC AND ACUPRESSURE IN THE DECREASE OF HYPERTENSION IN POSYANDU LANSIA SRONDOL BANYUMANIK SEMARANG - Nurhayati Nurhayati; Aisyah Nur Azizah; Amirul Kadafi; Mardiyono Mardiyono (Jurnal Riset Kesehatan, 2019)
Elderly Gymnastics, Acupressure, Hypertension, Elderly. Hypertension is the number one occurrence that causes death. Hypertension is a lifelong disease and treatment can be done using blood and using long-term anti hypertensive agents. The purpose of this study was to determine whether patients could make improvements in hypertensive patients at the Posyandu Srondol Banyumanik elderly. This type of research is quasi experimental design with a sample of 22 respondents, 11 respondents received treatment for elderly gymnastics while 11 respondents received acupressure treatment. The study was conducted once a week for 3 weeks with 60 minutes of elderly gymnastics and 10 minutes of acupressure. The results of this study prove that there were no significant differences in blood pressure before and after treatment. This is evidenced by the value of ρ more than 0.05. In addition from the results of the mean mean difference between acupressure and elderly gymnastics, it can be seen that acupressure is more effective in lowering blood pressure compared to elderly gymnastics. Conclusion: acupressure is more effective in lowering blood pressure than elderly exercise.